Meningkatkan Keterampilan Menulis Puisi Dengan Menggunakan Media Gambar di Kelas 4 SDN 2 Cimanggu Kecamatan Puspahiang Kabupaten Tasikmalaya - Rahmi Rahmawati; Riga Zahara Nurani; Fajar Nugraha (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
One effort to improve poetry writing skills in grade 4 students is to choose the rightmethod. In learning Indonesian, there is a lack of students' skills in writing poetry, low learning outcomes in poetry writing skills using inappropriate methods. The method used in this study is the image media method, which is a method for conveying material with a fun activity. This study aims to improve the poetry writing skills of grade 4 students at SDN 2 Cimanggu. This type of research is classroom action research consisting of two cycles which include planning, implementing, observing, reflecting. The research subjects were 20 grade 4 students at SDN 2 Cimanggu. Sources of data come from teachers and students. Data collection techniques using observation, written tests and documentation. The data collection instruments used were lesson plans, teacher observation sheets, student observation sheets and poetry writing assessment rubik. There is an increase in student learning outcomes after using media images. The results of the pre-action research showed that the average value of writing poetry was 58.25 with 20% student completeness, then cycle I learning activities with an average of 69 with 60% student completeness. Furthermore, in cycle II, students' learning abilities increased by an average of 76.25 with 85% student mastery. Thus image media can improve writing poetry for grade 4 students at SDN 2 Cimanggu.